Parlamentskii chas . Parlamentskii chas . Parliamentary Hour . Парламентский час - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Extra session of the Supreme Soviet of Russian Federation; situation on the Tajik-Afghan border; Russian Foreign Ministry policy. Contributors: Berdnikova, Nina (Anchor) Series description: A program about the activity of the Supreme Soviet of the Russian Federation. Внеплановое заседание сессии Верховного Совета Российской Федерации; положение на таджикско-афганской границе; политика российского Министерства иностранных дел. Создатели: Бердникова, Нина (Ведущий/Ведущая) Описание серии: Передача о деятельности Верховного Совета Российской Федерации.